The upper range of lumbar spine bone mineral density? An examination of the current world record holder in the squat lift - Dickerman, R. D.; Pertusi, R.; Smith, G. H. (International Journal of Sports Medicine, 2000)
Weight-bearing exercise is known to improve bone mineral density, however, excessive forces exerted on the lumbar spine can be pathologic. Cadaveric studies have calculated a hypothetical "critical compression force" at which the lumbar spine would suffer collapse. In addition, recent studies have suggested that bone density correlates with strength. Thus far studies have failed to examine elite power athletes to determine the possible upper range for bone mineral density and critical compression force. Therefore, we recruited the current world record holder in the squat lift, with a record squat lift >469 kg, for an examination of lumbar spine bone mineral density. The subject had dual energy x-ray absorptometry (DEXA) and magnetic resonance imaging (MRI) performed of the lumbar spine. The subject also had serum chemistries, cell blood count and testosterone levels performed. DEXA scan revealed the highest bone mineral density reported to date. MRI revealed normal alignment, no evidence of disc herniation or compressive disc disease. There was no frank or neural foraminal canal stenosis. The estimated compressive force generated on his lumbar spine during the squat lift of > 469 kg doubles the previously reported critical compression force. This case study supports the previously described relationship between strength and bone density and redefines the upper limits of bone density in strength athletes.